Sarah Kofman Eine Biographie - Feyertag, Karoline (Turia und Kant, 2014)
The first intellectual biography of the French-Jewish philosopher Sarah Kofmann (1934-1994) combines philosophical text analysis with contemporary theory of biography. The author conducts a critical revision of the postmodern maxim of the "Death of the Subject".